Generalized inequalities involving fractional operators of the Riemann-Liouville type - Bosch, Paul; Carmenate, Héctor J.; Rodríguez, José M.; Sigarreta, José M. (AIMS mathematics, 2022)
In this paper, we present a general formulation of the well-known fractional drifts of Riemann-Liouville type. We state the main properties of these integral operators. Besides, we study Ostrowski, Székely-Clark-Entringer and Hermite-Hadamard-Fejér inequalities involving these general fractional operators.